A Collision Tumor of Dermatofibrosarcoma Protuberance with Anaplastic Thyroid Carcinoma - Nurul Nadia Jamaluddin; Rohaizak Muhammad; Abdullah S SN; Yin P Wong (Jaypee Brothers Medical Publishers (P) Ltd, 2024)
Indexed by Scopus/ERA